Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1021/jm3011146
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Carprofen as a Multitarget Fatty Acid Amide Hydrolase/Cyclooxygenase Inhibitor

Abstract: Pain and inflammation are major therapeutic areas for drug discovery. Current drugs for these pathologies have limited efficacy, however, and often cause a number of unwanted side effects. In the present study, we identify the non-steroid anti-inflammatory drug, carprofen, as a multi-target-directed ligand that simultaneously inhibits cyclooxygenase-1 (COX-1), COX-2 and fatty acid amide hydrolase (FAAH). Additionally, we synthesized and tested several racemic derivatives of carprofen, sharing this multi-target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
75
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 59 publications
4
75
0
Order By: Relevance
“…FAAH showed no preference for either enantiomer, with each being more active than the racemate 10r . By contrast, in analogy to prior studies on different classes of FAAH/COX inhibitors, [30, 33] substantial differences were observed on COX-1 and COX-2. Compound (+)- 10r was highly potent on both COX-1 (IC 50 =0.29 nM) and COX-2 (IC 50 =50 nM), whereas (−)- 10r was weakly active on either target.…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…FAAH showed no preference for either enantiomer, with each being more active than the racemate 10r . By contrast, in analogy to prior studies on different classes of FAAH/COX inhibitors, [30, 33] substantial differences were observed on COX-1 and COX-2. Compound (+)- 10r was highly potent on both COX-1 (IC 50 =0.29 nM) and COX-2 (IC 50 =50 nM), whereas (−)- 10r was weakly active on either target.…”
Section: Resultssupporting
confidence: 52%
“…In addition to its high balanced potency, the highest reported thus far, [27, 28, 30, 32, 33, 65] we found that 10r displays no off-target activities on a panel of >90 biologically relevant targets, and effectively engages its intended targets after oral administration in mice. [51]…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…In conclusion, the development of dual FAAH-COX inhibitors would be of great potential value as a therapeutic strategy to treat different types of pain. Indeed, efforts are underway to synthesize such compounds (Favia, Habrant et al 2012; Cipriano, Bjorklund et al 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, benzothiazole, 29 b-lactam, 30 (thio)hydantoins 31 and some nonsteroidal anti-inammatory drugs (NSAIDs) [32][33][34] also have been reported to inhibit FAAH. Although the overall physiological role of FAAH has been reported, it is difficult to distinguish the function of FAAH in each specic tissue and organ.…”
Section: 28mentioning
confidence: 99%